The Effect of Motivation, Job Satisfaction and Employee Commitment to Work from Home Applied by the Company during the Covid-19 Pandemic (Case Study on Employees who have worked for more than 5 years) - Achmad Fauzi; Maya Sri Anindita; Juniawan Mandala Putra; Sarah Dewi Fakhrudin; Nila Putria; Anton Eka Saputra; Georgeus Geraldo (LPPM STIE EKA PRASETYA, 2022)
The Covid-19 pandemic itself entered Indonesia in March 2020, starting with a patient who was confirmed to have Covid-19 while attending an event in Jakarta where the patient had direct contact with a Foreign Citizen from Japan living in Malaysia. After the meeting, the patient complained of fever, cough and shortness of breath (WHO, 2020) and after an intensive examination, the patient was declared positive for Covid-19. Then the corona virus quickly spread to all corners of Indonesia. Until now, the implementation of WFH has become part of the new normal in our daily lives, so the implementation of telecommuting has become a necessity. This research was conducted in order to find out to what extent employees' influence on WFH or working from home affects their motivation, satisfaction or commitment to their work while working from home. Primary data were obtained from short interviews with completeness in the form of a questionnaire. The analysis used to determine the relationship between variables using SPSS 23.00 software. based on the results of the study, the researchers found that job satisfaction together had an effect on working from home/WFH. Partially, employee job satisfaction has a dominant effect on working from home.